Banking Industry Specific Determinants of Financial Distress: Empirical Evidence from ASEAN Countries - Saleem, Ramsha; Hussain, Altaf; Ibraheem, Ruqayya (iRASD Journal of Economics, 2020)
Recently, financial distress has become a significant issue, especially for the banking sector, that is considered as the backbone of the economy. Thus, the present study aim is to examine the effects of operating cash flow, profitability, financial leverage, trading activities and liquidity on financial distress of the banking industry of ASEAN countries. The researchers have extracted the data from the central banks of ASEAN countries for the year 2009 to 2018. The random effect model along with generalized method of moment (GMM) approaches have been used to check the predictors such as operating cash flow, profitability, financial leverage, trading activities and liquidity on financial distress of banking industry of ASEAN countries. The results revealed that all the predictors such as operating cash flow, profitability, financial leverage, trading activities and liquidity have a positive association with the financial distress of the banking industry of ASEAN countries. These outcomes provide the guidelines to the regulation-making authorities that they should enhance their focus on the issue of financial distress that could improve the financial position of the banks along with the country.